Improving the pH of Palm Oil Mill Effluent (POME) with Aerator Treatment and Water Dilution - Jaya, Galang Indra; Gunawan, Sri (Jurnal Biologi Tropis, 2024)
Palm Oil Mill Effluent/POME is a by-product produced from the processing of fresh fruit bunches/FFB into crude palm oil/CPO. Aeration of POME is one of the processing methods that aims to reduce the levels of organic matter and pollutants. This study aims to determine the dynamics of POME pH with aeration treatment and dilution variations in order to speed up the waste treatment time.The method used in this research is to make the treatment of pure POME, POME & water in a ratio of 1:1 & 1:2. The process carried out in the study was to place the solution into a 1 liter bottle and given an air flow using an aerator with a discharge of 0.66 l/min. POME samples were taken every 24 hours for a span of 7 days. The pH was measured using the electrometric method. On day 2, it was found that the pH of the 1:1 treatment POME had reached pH 6, while the 1:2 treatment on day 3 and the pure POME only reached pH 6 on day 5. Aeration is an effective method to neutralize the acidity of POME. The increase in POME pH was fastest in the 1:2, 1:1 and finally pure POME dilutions. All treatments met the pH quality standard on day 5. Aeration can help improve the quality of POME so that it is more environmentally friendly.